State dependence of monetary policy across business, credit and interest rate cycles - Sami Alpanda; Eleonora Granziera; Sarah Zubairy (Bank of Finland, 2019)
We investigate how the business, credit and interest rate cycles affect the monetary transmission mechanism, using state-dependent local projection methods and data from 18 advanced economies. We exploit the time-series variation within countries, as well as cross-sectional variation across countries, to investigate this issue. We find that the impact of monetary policy shocks on output and most other macroeconomic and financial variables is smaller during periods of economic downturns, high household debt, and high interest rates. We then build a small-scale theoretical model to rationalize these facts. The model highlights the presence of collateral and debt-service constraints on household borrowing and refinancing as a potential cause for state dependence in monetary policy with respect to the business, credit, and interest rate cycles.
URN:NBN:fi:bof-201909061439
Keywords: E21; E32; E52; 330